Penggunaan Budaya Perusahaan Terhadap SDM Toko Ritel dalam Menghadapi Era Disrupsi - Ellysa Lutfia Rahma (Universitas Pendidikan Nasional, 2021)
Today, we are faced with various changes in the fields of technology, culture, and economy,this is called the Disruption Era, which makes us have to be ready to adapt to existingconditions. This condition also affects Small and Medium Enterprises (SMEs) which areincluded in the important foundations of the Indonesian economy, one of which is in the retail business sector which is the most attractive field for entrepreneurs to start their business, because that is why retail businesses always experience developments in society, both in modern and traditional forms. Therefore, entrepreneurs must prepare various strategies in maintaining their business, starting from providing good service, providing quality goods, providing appropriate prices, and so on. This study uses a case study at Toko Pelangi Jaya in discussing the strategy of retail stores to maintain their business in the era of disruption by managing their employees through existing corporative culture values. By using qualitative research methods, this study will be presented in a descriptive form based on observations and interviews that have been conducted.